The effect of coach feedback on soccer competence in youth soccer players - Ambe, H.; Murase, K.; Ochiai, M.; Iteya, M.; Suzuki, N. (Japan Journal of Physical Education, Health and Sport Sciences, 2018)
The purpose of this study was to develop a self-perceived soccer-specific competence scale for youth players and to investigate the effects of coach feedback on the soccer competence of these players in actual competitive sport settings. Firstly, in order to develop the scale, the total of 611 Japanese male youth soccer players completed a questionnaire, which was composed of 60 items selected from a preliminary study. Participants were also asked to score their own ability as a soccer player out of a hundred. The players` scored assessment of their own ability was used as a criterion variable. Exploratory factor analysis revealed that soccer competence of youth players consisted of 9 sub-scales: passing and ball control with proper decision making, speed, motivation, endurance, dribbling skill, heading skill, defensive skill, physical strength and leadership. As the scale included individual ball techniques and group skill, physical fitness and mental fitness, which are essential elements of competitive soccer ability, it was considered to represent an adequate evaluation of selfperceived soccer competence in youth players. Additionally, players who had lower soccer ability scores showed significantly lower evaluation on the soccer competence scale than players who displayed higher scores. These results indicate that the soccer competence scale would provide a multi-dimensional and precise reflection of soccer competence in Japanese male youth players. Secondly, in order to investigate the effects of coach feedback on youth players` soccer competence, one coach and 15 male junior youth soccer club players participated in this study. The coach`s feedback to the players was recorded for 7 months using VTR and subsequently categorized into seven domains: (1) positive, (2) negative, (3) instructive, (4) questioning, (5) organizing, (6) friendly, and (7) other. Both before and after the observation period, players were asked to complete the soccer competence questionnaire derived in the first study. This revealed that competence related to passing and ball control with proper decision-making and dribbling skill increased significantly throughout the observation period. However, coach feedback did not significantly affect the longitudinal change in soccer competence. On the other hand, with regard to defensive skill, although no significant longitudinal change was confirmed during the observation period, there was a negative association between the frequency of negative feedback and the defensive skill score. Finally, the limitations of this study and future issues were discussed.